STRATEGI KOMUNIKASI HIDAYATULLAH DALAM MENANAMKAN NILAI-NILAI TOLERANSI DI KABUPATEN TANA TORAJA - Muhammad Saleh (Jurnal Dakwah Tabligh, 2021)
This research is Hidayatullah's communication strategy in instilling the values of religious tolerance in the Tana Toraja Regency. This study aims to determine Hidayatullah's communication strategy in instilling the values of religious tolerance in the Tana Toraja Regency. The research method used is descriptive qualitative with data collection methods of observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman data analysis technique, including data reduction, data presentation, and conclusion drawing. This study indicates three strategies carried out by the Hidayatullah Da'wah Institute in instilling the value of tolerance in the Tana Toraja Regency: (1). Through Gotong Royong Activities, all people in Tana Toraja attend this activity to create togetherness and brotherhood. (2). Through the Sports Sector, through this field, researchers consider that it will be successful if it is well managed and cared for (3). Through the Payroll system, where the Hidayatullah Institute will provide education about peaceful Islam, soft Islam. Researchers believe that the entire strategy carried out by the Hidayatullah Institute will make the community instill values of religious tolerance so that the majority and minority will continue to live side by side without any friction that causes conflict.